Alcoholism and The Baby Boomer Population : A Life Course Perspective - Lisa Phillips (Indian Journal of Gerontology, 2009)
Drinking alcohol is associated with many events in American culture. Many youth commemorate adulthood (turning the age of 21) by legally taking their first drink of alcohol. Families include alcohol in holiday traditions. Countless parties offer a variety of alcohol or instruct invitees to B.Y.O.B. on fliers (Bring your own beer). Advertisements for alcohol in newspapers, billboards, magazines and commercials are viewed daily by individuals too young to drink as well as those of age. None of the previously listed examples related to alcohol or alcohol consumption constitute alcohol addiction. However throughout one’s life course, the exposure to these messages related to drinking alcohol; and other factors can lead to the chronic illness referred to as alcoholism